INFLUENCE OF INQUIRY LEARNING MODEL AND REACHING ON LEARNING ACHIEVEMENT - Neffy Haryati; Alexon Alexon; Nina Kurniah (UNIB Press, 2018)
The purpose of this study was to determine the existence of a model of inquiry learning and reasoning on student achievement. This study uses an experimental method with a 2 x 2 factorial design, this study involved 54 students from a cluster random sampling of 82 grade V students of SDN Gugus I Sungai Rumbai. The analysis technique used was two-way ANOVA at a significant level of ?: 0.05 and continued with a T test. The results showed (1) student learning achievement taught with guided inquiry learning models was higher than the learning achievements of students studying with models free inquiry learning. (2) Students' learning achievement with high reasoning is higher than children with low reasoning. (3) There is influence on the interaction between inquiry and reasoning on student learning achievement. (4) Learning achievement of students who have high reasoning who follow the guided inquiry learning model is more effective than children who follow learning with the free inquiry model. (5) The learning achievement of students with low reasoning who participate in guided inquiry learning is lower than free inquiry. This study proves that the learning achievements of students who have high reasoning who follow guided inquiry learning are higher than students who follow free inquiry learning.